If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4p + 8p + -10 = 2 + 9p Reorder the terms: -10 + 4p + 8p = 2 + 9p Combine like terms: 4p + 8p = 12p -10 + 12p = 2 + 9p Solving -10 + 12p = 2 + 9p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-9p' to each side of the equation. -10 + 12p + -9p = 2 + 9p + -9p Combine like terms: 12p + -9p = 3p -10 + 3p = 2 + 9p + -9p Combine like terms: 9p + -9p = 0 -10 + 3p = 2 + 0 -10 + 3p = 2 Add '10' to each side of the equation. -10 + 10 + 3p = 2 + 10 Combine like terms: -10 + 10 = 0 0 + 3p = 2 + 10 3p = 2 + 10 Combine like terms: 2 + 10 = 12 3p = 12 Divide each side by '3'. p = 4 Simplifying p = 4
| 5y-2(-33+6y)=31 | | 2(a^2)-4=68 | | 2t^2-9t-21=0 | | 15/4=30/m | | 5-2(-33+6y)=31 | | x+1-2=3x-1 | | 5x+14-8x=19-13x+10x-5 | | s=2s-8 | | (1/2)x^4-(1/8)x^2=0 | | 6-9x+12=0 | | 1/2x^4-1/8x^2=0 | | 18x+8=7x+8 | | Log^2(4x-7)=1 | | 2-b=4b-7b+10 | | 8x-4x-8=16 | | 12x+21=3x+19 | | .22y-.04=.12y+1-.6y | | 8x-4x+8=16 | | -m+9=-2m-1 | | (9x-4)-(-2x+1)= | | -9(v+3)=-4v-42 | | -5-6x=12 | | 15+20x-2=93 | | Ln(9x+6)=ln(5x-30) | | 5s-28=-16+9s | | 2x^2+3x=7x | | 10-8k=-10k-10 | | 37/21x/1 | | (9x+5)-(3x+1)= | | 1122=93.5 | | 6[3y-2(y-1)]-2-7y=0 | | 8(p-9)=72 |